2007
DOI: 10.1128/jb.01354-06
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide in Chemostat-Cultured Escherichia coli Is Sensed by Fnr and Other Global Regulators: Unaltered Methionine Biosynthesis Indicates Lack of S Nitrosation

Abstract: We previously elucidated the global transcriptional responses of Escherichia coli to the nitrosating agent S-nitrosoglutathione (GSNO) in both aerobic and anaerobic chemostats, demonstrated the expression of nitric oxide (NO)-protective mechanisms, and obtained evidence of critical thiol nitrosation. The present study was the first to examine the transcriptome of NO-exposed E. coli in a chemostat. Using identical conditions, we compared the GSNO stimulon with the stimulon of NO released from two NO donor compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
122
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 77 publications
8
122
1
Order By: Relevance
“…Nevertheless, ''physiological'' amounts of NO do not stimulate the SOS response in Salmonella enterica because RecA is not essential to prevent NO-dependent bacterial DNA fragmentation (32). Moreover, several transcriptomic analysis of E. coli demonstrated that expression of the genes of the SOS response was not enhanced following exposure to NO (18)(19)(20)(21). Additionally, we observed that stx2 mRNA expression was not modulated when bacteria were treated at the same time with mitomycin C and NOR-4.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Nevertheless, ''physiological'' amounts of NO do not stimulate the SOS response in Salmonella enterica because RecA is not essential to prevent NO-dependent bacterial DNA fragmentation (32). Moreover, several transcriptomic analysis of E. coli demonstrated that expression of the genes of the SOS response was not enhanced following exposure to NO (18)(19)(20)(21). Additionally, we observed that stx2 mRNA expression was not modulated when bacteria were treated at the same time with mitomycin C and NOR-4.…”
Section: Discussionmentioning
confidence: 60%
“…Cellular production of NO requires the enzyme NO synthase that oxidizes L-arginine as a substrate; the calciumindependent inducible NO synthase (iNOS) isoform is expressed in numerous cells, e.g., enterocytes, in response to type 1 cytokines (16). High output of iNOS-derived NO is cytotoxic for pathogenic bacteria (17) or may induce transcriptomic changes (18)(19)(20)(21) by interacting with different NO sensors such as the nitrite-sensitive repressor (NsrR), a key regulator of the nitrosative stress in enterobacteria (22,23). NsrR DNA-binding activity is suppressed by NO, yielding to the expression of various genes involved in NO detoxification.…”
mentioning
confidence: 99%
“…In approximately 80 % of the community-acquired urinary tract infections (UTIs) the cause of the infection is a uropathogenic Escherichia coli (UPEC) strain. Flavohemoglobin (Hmp) and flavorubredoxin (NorV) are the two main NO-detoxifying systems in E. coli and are up-regulated in response to NO and nitrosating agents such as S-nitrosoglutathione [5,6,7,8]. The main function of Hmp is to catalyse the conversion of NO to nitrate [9,10], but Hmp can also operate in anaerobic conditions reducing NO to nitrous oxide (N 2 O) [11].…”
mentioning
confidence: 99%
“…The suf operon is subject to complex regulation, with roles for OxyR, Fur, IscR and IHF in controlling activity of the suf promoter (Lee et al, 2003(Lee et al, , 2004(Lee et al, , 2008Yeo et al, 2006). There is evidence that the suf genes are upregulated by exposure to NO (Justino et al, 2005;Pullan et al, 2007), and of an NsrR binding site in the sufA promoter (Partridge et al, 2009). Our microarray data showed modest de-repression of suf genes in an nsrR mutant, although the statistical cut-off was not met for the DnsrR/ AUG nsrR comparison.…”
Section: Nsrr Regulates Expression Of the Suf Iron -Sulfur Cluster Rementioning
confidence: 99%